Technical Efficiency of Poultry Egg Producers in Oyo State of Nigeria - Binuomote, S.O.; Ajetomobi, J.O.; Ajao, A.O. (International Journal of Poultry Science, 2008)
The study analyzed the Technical Efficiency (TE) of poultry egg producers in Oyo state of Nigeria using a Cobb-Douglas stochastic production frontier function. The data for the study were collected using structured questionnaire administered on random samples of 51 poultry egg producers. The results showed that, the TE of farmers varied between 0.10 and 0.99 with a mean of 0.823. About 90% of the farmers surveyed had technical efficiency score of >0.70. The analysis showed that stock of birds is the most important determinant of poultry egg production while years of experience, management system, educational level and family size are the socioeconomic characteristic influencing the farmers’ technical efficiency. The findings show that further productivity gains linked to the improvement in TE may still be realized in poultry egg production in Nigeria.